Integrating cytogenetics and genomics in comparative evolutionary studies of cichlid fish - Mazzuchelli, Juliana [UNESP]; Kocher, Thomas David; Yang, Fengtang; Martins, Cesar [UNESP] (Biomed Central Ltd., 2012)
Background: The availability of a large number of recently sequenced vertebrate genomes opens new avenues to integrate cytogenetics and genomics in comparative and evolutionary studies. Cytogenetic mapping can offer alternative means to identify conserved synteny shared by distinct genomes and also to define genome regions that are still not fine characterized even after wide-ranging nucleotide sequence efforts. An efficient way to perform comparative cytogenetic mapping is based on BAC clones mapping by fluorescence in situ hybridization. In this report, to address the knowledge gap on the genome evolution in cichlid fishes, BAC clones of an Oreochromis niloticus library covering the linkage groups (LG) 1, 3, 5, and 7 were mapped onto the chromosomes of 9 African cichlid species. The cytogenetic mapping data were also integrated with BAC-end sequences information of O. niloticus and comparatively analyzed against the genome of other fish species and vertebrates.Results: The location of BACs from LG1, 3, 5, and 7 revealed a strong chromosomal conservation among the analyzed cichlid species genomes, which evidenced a synteny of the markers of each LG. Comparative in silico analysis also identified large genomic blocks that were conserved in distantly related fish groups and also in other vertebrates.Conclusions: Although it has been suggested that fishes contain plastic genomes with high rates of chromosomal rearrangements and probably low rates of synteny conservation, our results evidence that large syntenic chromosome segments have been maintained conserved during evolution, at least for the considered markers. Additionally, our current cytogenetic mapping efforts integrated with genomic approaches conduct to a new perspective to address important questions involving chromosome evolution in fishes.
Keywords: Cichlidae; Genome evolution; Molecular cytogenetics; Chromosome; Linkage groups; BACs